Vpliv življenjskega sloga na razvoj nevrodegenerativnih bolezni - Slatinek, Vesna (Placebo, 2024)
The impact of lifestyle on the development of neurodegenerative diseases is complex and involves many factors, such as obesity, diet, which has an impact on gut microbiota, physical activity, and educational attainment. Obesity contributes to chronic inflammation that can damage the brain, while changes in the gut microbiota can exacerbate neuroinflammation. Education plays an important role in developing cognitive reserve and promoting a healthy lifestyle, which can reduce the risk of neurodegenerative diseases and improve treatment outcomes. Despite the progress already made, this area is still the subject of intensive further research, which will be crucial to better understand the mechanisms behind the association between lifestyle and neurodegenerative diseases.
Keywords: črevesna mikrobiota; Debelost; izobrazba; Nevrodegenerativne bolezni; prehrana; življenjski slog